발음중심과 의미중심 지도방법이 정신지체아, 학습지진아 및 비장애아의 초기 단어읽기에 미치는 효과 비교 - 여광응(Kwang-Eung Yeo); 조애령(Eae-Ryung Cho); 이점조(Jum-Jo Lee) (언어치료연구, 2002)
The purpose of this study is to find out the effective reading method of mental retarded, slow leaner and normal children in real educational case by verifying if there are any differences among those three groups whose IQ level is different in improving the ability of an early-stage word-reading by reading instruction method(articulation-based, meaning-based), and if there are in improving the ability of an early-stage word-reading by word presentation form.The subjects were 15 MR, 16 SL and 16 NC who were the same mental age, sample from a special school, special classes in the elementary schools and kindergarten in Masan city.The main conclusions were as follows.First, Comparing articulation-based and meaning-based instruction methods effect on improvement of an early-stage word-reading ability of those groups whose mental age is same(5 years old), when they were taught by articulation-based, MR and SL groups were inferior to NC group conspicuously and when they were taught by meaning-based instruction method, there were not meaningful differences among them.Secondly, to the same mental age groups of MR, SL, NC, when three groups were compared if the non-meaning word and word-in-sentence presentation influence on the early-stage word-reading of ability, there was no differences in reading ability in those three groups, when those groups were presented the non-meaning word. In this result, it seems that it's difficult to read non-meaning word by any instruction methods. KCI Citation Count: 5